The historical archaeology of the Ottoman Empire : breaking new ground - Baram, Uzi, 1964-; Carroll, Lynda, 1971- (Contributions to global historical archaeology., 2000)
Archaeology in the Middle East and the Balkans rarely focuses on the recent past; as a result, archaeologists have largely ignored the material remains of the Ottoman Empire. Drawing on a wide variety of case studies and essays, this volume documents the emerging field of Ottoman archaeology and the relationship of this new field to anthropological, classical, and historical archaeology as well as Ottoman studies.